Comparison Between Below Knee Contrast Enhanced Tomographic 3D Ultrasound and CT, MR or Catheter Angiography for Peripheral Artery Imaging. (March 2021) - Rogers, Steven; Carreira, Joao; Phair, Alison; Olech, Christabel; Ghosh, Jonathan; McCollum, Charles
Abstract : Objective: Clear imaging of below knee and foot arteries is essential to plan distal reconstructions. Contrast enhanced tomographic 3D ultrasound (CEtUS) is novel and entirely safe with no exposure to ionising radiation or nephrotoxic contrast. In the present study, inter- and intra-observer agreement of CEtUS was calculated, and compared with below knee angiography. Methods: In the same week as computed tomography, magnetic resonance or catheter angiography, CEtUS was performed using intravenous 1.2 mL bolus injections of Sonovue with a maximum of 5 mL administered per patient. CEtUS was reported by a vascular scientist blinded to the angiograms reported by a consultant radiologist. Images were compared using a modified Society of Vascular Surgery (SVS) runoff score. Results: Of the 181 patients recruited with peripheral arterial disease, 20 were excluded from analysis as they withdrew consent, could not be cannulated, or their images were non-diagnostic. In the remaining 161 patients, there were 175 comparative patient images split into two groups: 81 had calf imaging and 94 had pedal imaging representing 405 and 198 imaged arteries, respectively. Weighted quadratic kappa/ICC values for intra- and inter-observer agreement were excellent (κ/ICC = 0.83 to 0.95) and had narrow confidence intervals in both groups. When comparing angiography and CEtUS, weighted quadratic κ/ICC agreement was moderate with acceptable confidence intervals in both groups (Calf κ/ICC = 0.54; Pedal κ/ICC = 0.53). Agreement decreased from popliteal to pedal vessels as diameter decreased. Agreement between CEtUS and digital subtraction angiography was best, and computed tomography angiography the weakest. Conclusion: CEtUS is a novel imaging modality with strong observer agreement that achieves clear peripheral and foot images without ionising radiation exposure or nephrotoxic X-ray contrast media. CEtUS enhances visualisation of runoff vessels, which may play a role in planning of limb salvage or targeted assessment.